2011
DOI: 10.1007/s10549-011-1706-9
|View full text |Cite
|
Sign up to set email alerts
|

First generation prognostic gene signatures for breast cancer predict both survival and chemotherapy sensitivity and identify overlapping patient populations

Abstract: The aims of this study were to compare the performance of six different genomic prognostic markers to predict long-term survival and chemotherapy response on the same patient cohort and assess if clinicopathological variables carry independent prognostic and predictive values. We examined seven clinical variables and six previously described prognostic signatures on 228 tumors from patients who received homogeneous preoperative chemotherapy and had long-term follow-up information for survival. We used the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The other covariates, including PgR status, tumor size, nodal status, and type of surgery, may have distinct prognostic power independent of proliferative markers such as histological grade and IHC Ki67. Iwamoto et al (15) reported similar results indicating that clinical variables remained predictive of survival or chemotherapy response independent of genetic markers. As a well-established cell proliferation marker in breast cancer, IHC Ki67 is an excellent candidate biomarker for luminal B tumors in ER-positive cases.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The other covariates, including PgR status, tumor size, nodal status, and type of surgery, may have distinct prognostic power independent of proliferative markers such as histological grade and IHC Ki67. Iwamoto et al (15) reported similar results indicating that clinical variables remained predictive of survival or chemotherapy response independent of genetic markers. As a well-established cell proliferation marker in breast cancer, IHC Ki67 is an excellent candidate biomarker for luminal B tumors in ER-positive cases.…”
Section: Discussionmentioning
confidence: 77%
“…Also, genomic markers with multiple genes were assessed by average gene expression based on data normalized using the MAS5 algorithm, and log 2-converted mRNA gene expression data, a departure from the original methods used in similar published reports. (15) For determining prognosis and predicting sensitivity to chemotherapy, gene expression profiling (by, for example, the 21-gene or 70-gene signatures) remains the gold standard. Nevertheless, we suggest that IHC Ki67 could emerge as a cost-effective alternative, defined and validated for worldwide clinical diagnostic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high tumor proliferation rate is associated with higher probability of pCR but also with worse prognosis (25), although high tumor infiltrating lymphocyte count is associated with higher pCR rate and better prognosis (26,27). Many similar, yet to be identified, interactions between prognostic markers and pCR may exist.…”
Section: Discussionmentioning
confidence: 99%
“…However, each of the tests relies on a different set of genes, with only a modest overlap between assays, and therefore may assign a different risk category to the same patient. Although several studies examined classification overlap among various genomic prognostic tests using proxy models, such as gene expression array-based unofficial versions of Oncotype DX and modified versions of published assays [20,21], no direct comparison of any two commercially available assays in the same patient population has been reported to date. An imminent clinical challenge for practicing physicians is to understand how different assays relate to each other and what to expect when more than one assay is used for the same cancer.…”
Section: Introductionmentioning
confidence: 99%